If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 24) = x Reorder the terms: (24 + 2x) = x Remove parenthesis around (24 + 2x) 24 + 2x = x Solving 24 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 24 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 24 + 1x = x + -1x Combine like terms: x + -1x = 0 24 + 1x = 0 Add '-24' to each side of the equation. 24 + -24 + 1x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 1x = 0 + -24 1x = 0 + -24 Combine like terms: 0 + -24 = -24 1x = -24 Divide each side by '1'. x = -24 Simplifying x = -24
| 3x^2-33x=0 | | (1+8x)(1+8x)=0 | | 5y-6+y+46=6y+40-2y | | -6x-7x=-52 | | 2(3+5x)-3=23 | | 6t^5+3t^4=-12t^3 | | 9x+5=9-(9x-3) | | 21x-28y+7=0 | | 49w^2-81g^2=0 | | e^9x+8=13 | | 81v^2-126v+49= | | 900x^2-1800x+900=0 | | x^2+14x+15= | | 4w^2+28wd+49d^2=0 | | t^2-3.2t-3.2=49 | | 40x^2+30x=0 | | 4r^2-36r+81=0 | | b^4-144=0 | | 5(9c^2-64)=0 | | 45c^2-32= | | -5x^3+4x^2=0 | | 3y^2+8y=12y+15 | | 7(x+1)-6x=-3 | | 5x-3=8x+12 | | 4x+2x-5=7 | | 15a^2-17ab-4b^2=0 | | 5x-4=7x+6 | | 8b^2-18bc-5c= | | 3(4)+3= | | 12s^3+20s^2-48s= | | 3(4x-7)=7x-3 | | x^2+17x+72= |